2020
DOI: 10.1145/3415207
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Shared Gaze on Audio- Versus Text-Based Remote Collaborations

Abstract: Remote collaborations are becoming ubiquitous, but, despite their many advantages, face unique challenges compared to collocated collaborations. Visualizing the collaborator's point of gaze on a shared screen has been explored as a promising way to alleviate some of these limitations by increasing shared awareness. However, prior studies on shared gaze have not considered the medium of communication and have only studied its effect on audio. This paper presents a study that compares the effects of shared gaze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Afterwards, a few works [14,15,27,47] captured the eye gaze signal through the eye tracker for collaborative reading, writing, problem-solving, and learning. Later on, the authors in [28,49] explored acoustic signal along with the eye gaze for improving the remote collaborative performance. While eye gaze monitoring by eye tracker is a promising technique, the cost and availability of the tracker to all the students is a major obstacle.…”
Section: Dedicated Device-based Approachmentioning
confidence: 99%
“…Afterwards, a few works [14,15,27,47] captured the eye gaze signal through the eye tracker for collaborative reading, writing, problem-solving, and learning. Later on, the authors in [28,49] explored acoustic signal along with the eye gaze for improving the remote collaborative performance. While eye gaze monitoring by eye tracker is a promising technique, the cost and availability of the tracker to all the students is a major obstacle.…”
Section: Dedicated Device-based Approachmentioning
confidence: 99%
“…Body metrics (e.g., amount of movement [27,52,91,92], distance between members [58,59]) achieved a high rate of success for hands-on tasks while being generalizable across different contexts. Combinations of verbal (e.g., speech participation [25,27,29,30]) and gaze metrics (e.g., area of interest [78], joint visual attention [26,70,77,83,86]) were usually successfully linked to increased performance, although one paper found low-level gaze features to be unsuccessful predictors [72]. Physiological metrics, on the other hand, were largely unsuccessful and there was notable divergence in the success levels of physiological synchrony [62,63,65,66].…”
Section: Product: Performancementioning
confidence: 99%
“…Other notable findings revealed that body distance was significantly related to physical engagement [79]. Additionally, during voice-based communication between collaborators, the presence of shared gaze reduced cognitive workload, potentially because it provided a shared referent [86]. However, the authors also suggest that, in text-based communication, shared gaze may increase cognitive load since participants must divide their attention.…”
Section: Process: Individual Cognitive Processesmentioning
confidence: 99%
See 2 more Smart Citations